Musculoskeletal involvement in sarcoidosis - Akasbi Nessrine; Abourazzak Fatima Zahra; Harzy Taoufik (Jornal Brasileiro de Pneumologia, 2014)
Sarcoidosis is a multisystem inflammatory disorder of unknown cause. It most commonly affects the pulmonary system but can also affect the musculoskeletal system, albeit less frequently. In patients with sarcoidosis, rheumatic involvement is polymorphic. It can be the presenting symptom of the disease or can appear during its progression. Articular involvement is dominated by nonspecific arthralgia, polyarthritis, and Löfgren's syndrome, which is defined as the presence of lung adenopathy, arthralgia (or arthritis), and erythema nodosum. Skeletal manifestations, especially dactylitis, appear mainly as complications of chronic, multiorgan sarcoidosis. Muscle involvement in sarcoidosis is rare and usually asymptomatic. The diagnosis of rheumatic sarcoidosis is based on X-ray findings and magnetic resonance imaging findings, although the definitive diagnosis is made by anatomopathological study of biopsy samples. Musculoskeletal involvement in sarcoidosis is generally relieved with nonsteroidal anti-inflammatory drugs or corticosteroids. In corticosteroid-resistant or -dependent forms of the disease, immunosuppressive therapy, such as treatment with methotrexate or anti-TNF-α, is employed. The aim of this review was to present an overview of the various types of osteoarticular and muscle involvement in sarcoidosis, focusing on their diagnosis and management.